TPACK Capability Analysis Students of Biology Education Study Program on Animal Physiology Learning with Online Learning Models - Ristianafi, Diana Putri; Isnaeni, Wiwi; Widiyatmoko, Arif (Journal of Innovative Science Education, 2023)
The aim of education in Indonesia is to educate the life of the nation. In an effort to realize the goals of Indonesian education, a teacher as an educator must understand and have Technological Pedagogical Content Knowledge (TPACK) skills, especially during the Covid 19 pandemic which requires learning to be done online. One of the subjects that develops TPACK abilities is Animal Physiology at the Department of Biology, Semarang State University. The purpose of this study: 1) Knowing the process of implementing Online Learning which is carried out in Animal Physiology lessons can improve the TPACK abilities of Biology Education study program students. 2) Knowing the TPACK ability level of Biology Education study program students after participating in Online Learning Animal Physiology. This research is a mixed method research with an explanatory sequential design. Selection of the sample by purposeful sampling. The research population is all students majoring in Biology class of 2019. The research sample is students of the Biology Education Study Program Classes B and C who are taking the Even Semester Animal Physiology course in the 2020/2021 academic year. The results showed that learning Animal Physiology online by using project assignments can foster TPACK abilities in Biology Education study program students. TPACK's capabilities can be seen and observed from the initial online learning meeting activities to the completion of project assignments.